Analysis Of Effectiveness Of Online Learning Pandemic Covid-19 In Prosthetic Orthotic Major In Polkesta - Nur Rachmat (Poltekkes Kemenkes Surakarta, 2020)
Background: Prosthetic Orthotics Major in Polkesta conducts online lectures in order to support government efforts in the even semester 2019/2020, starting from March 2020 until the end of the even semester. Several online applications are used in support of online lectures. This study was conducted to analyze the effectiveness of online learning during the covid-19 pandemic in the orthotic prosthetic Major in Polkesta Indonesia. Methods: This is quantitative descriptive study. This research uses survey method using online Google Form questionnaire. The population is students of Prosthetic Orthotic Major, There are 322 respondents who are willing to contribute in the research. Data obtained through filling in questions that are shared with all respondents in the form of google form. Then the collected data was analyzed and described. The components contained in the questionnaire consisted of several questions, namely (1) Do you understand online learning at the time of the Covid-19 Pandemic; (2) Do you think online learning at Prosthetic Orthotic Major Polkesta was effective; (3) Which online application is used for online learning that is effective in your opinion; (4) Which online learning model do you feel effective; (5) Types of assignments that make you understand during online learning; (6) What media do you use when implementing online learning; (7) are there any obstacles when you carry out online learning (8) What obstacles do you face when implementing learning. Results: there are 67 % of students felt less effective, 14% of students felt ineffective, 20 % of students felt effective. Applications used by students and felt to be effective are Google meet, google classroom, WhatsApp Group. Learning methods using Life video conferencing are felt to be the most effective. Conclusion: Online learning process in the prosthetic orthotic major is not felt to be quite effective by students.